Role of Methyl thiobutyrate to Botrytis cinerea on cucumber - Chang, Nv; Liu, Rui; Lu, Cuihua; Lai, Yuqing; Xu, Qian; Yang, Yuhong; Li, Yan; Ling, Jian; Xie, Bingyan; Zhao, Wenchao; Mao, Zhenchuan; Zhao, Jianlong (Frontiers in Plant Science, 2025)
IntroductionBotrytis cinerea is a major agricultural pathogen that causes significant economic Q7 losses worldwide, affecting various crops, including cucumbers. Developing environmentally sustainable control strategies for this pathogen is crucial. Methyl thiobutyrate (MTB), a small organic molecule identified in the volatile organic compounds (VOCs) of biocontrol bacteria, has demonstrated potential in inhibiting B. cinerea both in vitro and in vivo.MethodsIn this study, the efficacy of MTB against cucumber gray mold disease was examined by assessing the in vitro and in vivo activities of MTB against B. cinerea and analyzing the transcriptomic data from MTB-treated cucumber leaves infected with B. cinerea.Results and discussionThis study shows that a 2 mg/mL solution of MTB inhibits B. cinerea growth by 98.6% in vitro. In vivo, MTB effectively reduces B. cinerea infection in cucumbers, alleviates necrotic damage in leaf tissues, and significantly reduces disease severity. Transcriptomic analysis reveals that MTB activates the plant immune responses by modulating key MAPK cascade signaling genes and upregulating basal defense genes, including chitinase, pectinase, and lignin biosynthesis genes. Furthermore, MTB influences the signaling pathways of salicylic acid (SA), jasmonic acid (JA), and ethylene (ET), resulting in the upregulation of genes such as peroxidase (POD), phenylalanine ammonia-lyase (PAL), lipoxygenase (LOX), and ethyleneresponsive transcription factors (ERFs). These results demonstrate the potential of MTB as an effective biocontrol agent against B. cinerea and provide valuable insights into its underlying mechanisms of action.